Control as an approach to preventing burnout among health care personnel - Veríssimo, R. (2003)
The burnout syndrome may be understood as a result of sustained physiological activation upcoming from occupational stress, together with the failure of the subject to cope with job situation—at stimulus level or on consequent reaction. Under this model, one can put forward two main conditions to prevent burnout through emotional regulation: (1) awareness of the uneasiness on the part of the subject enabling him to (2) act over those demands. The aim of the present study was to gain additional information about the relationship between burnout and control. With a mean age of 33.6 years (S.D.=9.06), subjects were 273 oncology nurses (33 men and 240 women) with direct care responsibilities. All subjects completed the Portuguese adaptations of the Maslach Burnout Inventory, to assess the burnout syndrome, and the Working Conditions and Control Questionnaire, which elicits six job control aspects. The correlations between MBI and control show that individuals who reported greater control feel more personal accomplishment, decreased emotional exhaustion, and display less depersonalization. Moreover, prediction of burnout through regression analysis shows that it is highly dependent of all control variables. These findings are consistent with the hypothesis that burnout is mostly due to the lack of control over stressful work conditions.